2008
DOI: 10.1093/ndt/gfn008
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer in renal transplant recipients

Abstract: Our results showed that RTR are at risk for early occurrence and for locally advanced prostate cancer, especially when they received a CNI and AZA maintenance immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…Diagnoses were made earlier in life, at approximately 60 years of age [18]. Such data should justify proposing a PC screening to solid organ transplant recipients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Diagnoses were made earlier in life, at approximately 60 years of age [18]. Such data should justify proposing a PC screening to solid organ transplant recipients.…”
Section: Discussionmentioning
confidence: 97%
“…However, no evidence suggests a specific effect on prostate carcinoma. Only 1 study demonstrated potential carcinologic effects of CINinhibitor and azathioprine on the prostate [18]. It is therefore difficult to recommend any immunosuppressive regimen modifications after PC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some suggestion that immunosuppression can affect the natural history of CaP. Kleinclauss et al [9] reported a high rate of T3/4 disease (36%) and metastasis (19.3%) at presentation in renal transplantation patients and that addition of azathioprine to calcineurin inhibitors was the only independent risk factor for higher-stage disease. Another recent study showed an increased incidence of CaP in renal transplantation patients who were treated with sirolimus when compared with that in those treated with other therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study highlighted that prostate cancer appears sooner, with a higher rate of advanced or metastatic disease in RTR than in the general population. 20 …”
Section: Discussionmentioning
confidence: 99%